EFEKTIVITAS PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION TERHADAP PEMBELAJARAN MENULIS TEKS NEGOSIASI SISWA KELAS X DI SMAN 1 CISARUA - Nasution, Humairah Zahrah; Syarifah Aeni, Eli; Aryana, Suhud (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Writing is a skill that students must master, one of which is writing negotiation texts. This research aims to help students learn to write negotiation texts using the Group Investigation type Cooperative Learning model and determine the effectiveness of its use in learning to write negotiation texts. The research was conducted at SMAN 1 Cisarua in class X with 30 students. This research is a quantitative type with a Pre-Experimental method in the form of One Group Pretest-Posttest. This is to obtain data on descriptive test results (pretest and posttest) which will be explained descriptively. The data was tested using the Wilcoxon Test and N-Gain Test used with SPSS vers 22 and Microsoft Excel. Results say that obtained there is an influence of using the Group Investigation type Cooperative Learning model in learning to write negotiation texts. With an increase of 0.55 at the medium level and an effectiveness result of 55.8% at the effective level.